Tuberculosis treatment and nutritional status among the tribals of Northeast India - Tungdim, Mary Grace; Kapoor, Satwanti (Acta Biologica Szegediensis, 2008)
The data for the present study was collected cross-sectionally among a total sample of 247 adult tribal males between the age 20-40 years inhabiting Manipur, Northeast India. The subjects comprised of TB patients and healthy non-patients taken as control group (CG). The TB patients were categorized into three groups viz.: Before starting treatment (BST), after 2 months of treatment (2MOT), after completion of treatment(ACT). Anthropometric measurements like weight, height and mid upper arm circumference were taken for the study. The index of nutritional status like body mass index(BMI) was computed. The percentage of chronic energy deficiency (CED) based on body mass index (BMI<18.5kg/m2) for the different groups of subjects were 64.5%(BST), 49%(2MOT), 34%(ACT) and 6.3%(CG) respectively. The CED based on mid upper arm circumference (MUAC<22.0cm) was found to be 43.5%(BST), 30.9(2MOT), 26%(ACT) respectively. Based on the World Health Organization BMI classification, the prevalence of CED (BMI<18.5kg/m2) among tuberculosis patients in the different stages of treatment was from high to very high indicating a critical situation. The prevalence of undernutrition based on MUAC among the TB patients was also clearly evident but not so in healthy non patient subjects. Regular intake of medicine is clearly reflected in significant improvement in nutritional status indices.